A Case of Cornelia de Lange Syndrome: Difficulty in Prenatal Diagnosis - Tadatsugu Kinjo; Keiko Mekaru; Miyuki Nakada; Hayase Nitta; Hitoshi Masamoto; Yoichi Aoki (Hindawi Limited, 2019)
We report a case of Cornelia de Lange syndrome (CdLS) where prenatal diagnosis was not made even with major anomaly. A 33-year-old Japanese woman was referred to our institution at 23 weeks of gestation because of fetal forearm defect. Ultrasound examination revealed short forearms and short humeri and femurs (-2.1 SD). The fetal estimated body weight was 450 g (-1.3 SD). Fetal MRI at 26 weeks of gestation revealed short forearms and hypoplasty of hand fingers. Fetal growth restriction became evident thereafter, leading to intrauterine fetal death occurring at 29 weeks of gestation. A stillbirth baby was of 798 g in body weight and 33.0 cm in length. External examination showed a low hairline, synophrys, low-set ear, hypertrichosis, and smooth long philtrum with thin lips. The neck appeared short and broad. Finally, CdLS was diagnosed. The prenatal diagnosis might be possible as the arm findings were totally characteristic in a small fetus, regardless of whether an overhanging upper lip was identified. Because CdLS is a rare condition, it is important to consider its possibility as a part of differential diagnosis.